2017
DOI: 10.1080/03630242.2017.1342740
|View full text |Cite
|
Sign up to set email alerts
|

Irregular menstruation according to occupational status

Abstract: This cross-sectional study explored associations of irregular menstruation with occupational characteristics, using secondary analyses of data from 4,731 women aged 19-54 years, collected from a nationally representative sample, the Korea National Health and Nutrition Examination Survey-V during 2010-2012. The associations between irregular menstruation and occupation were explored using multiple logistic regression. Compared to non-manual workers, service/sales workers had a greater odds of irregular menstrua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…To our knowledge, this is the largest study that described the regularity and length of menstrual cycles in young Korean women. The proportion of women reporting irregular cycles in our study was higher times more likely to have irregular cycles than daytime workers [39]. Nurses are the largest healthcare workforce [40] and subjected to a challenging work environment (e.g., shift work and physically demanding tasks) [41].…”
Section: Discussionmentioning
confidence: 67%
“…To our knowledge, this is the largest study that described the regularity and length of menstrual cycles in young Korean women. The proportion of women reporting irregular cycles in our study was higher times more likely to have irregular cycles than daytime workers [39]. Nurses are the largest healthcare workforce [40] and subjected to a challenging work environment (e.g., shift work and physically demanding tasks) [41].…”
Section: Discussionmentioning
confidence: 67%
“…In a previous study, menstrual cycle length variations were more frequently observed with increasing age in women from lower social groups [ 28 ]. Manual workers and service/sales workers showed a higher frequency of irregular menstruation [ 21 , 29 ]. Lifestyle and psychological risk factors, such as smoking, obesity and stress were significantly associated with menstrual irregularity [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the study results differed depending on whether the father or mother worked for long hours suggests a problematic situation regarding the difference in distribution of duties in the family. The imbalance in the burden of household work between men and women in the family may make women more vulnerable to health risks ( 34 , 35 ). The results of this study also showed that the effects of long working hours on children's dyslipidemia were associated with a significantly increased risk only for mothers.…”
Section: Discussionmentioning
confidence: 99%